Perspectives of LGBTQA+ young people on suicide prevention services in Australia - Rigel Paciente; Helen Morgan; Angus Cook; Yael Perry; Ashleigh Lin; Penelope Strauss (Elsevier, 2024)
LGBTQA + people are less likely to access mental health care despite an increased risk of adverse mental health outcomes including suicidal thoughts and behaviours. The present study aimed to explore Australian LGBTQA + young people's perceptions of key factors associated with access to suicide prevention services. A qualitative design, utilising inductive thematic analysis, was employed to explore participants' experiences within different service settings. Twenty-seven LGBTQA + young people who had experienced suicidal thoughts and/or behaviours took part in this study. LGBTQA+ and general service accessibility concerns were reported by participants. Themes pertaining to LGBTQA + -inclusive practices were more commonly reported to be a barrier. Whereas visibility of LGBTQA + -inclusive practice was reported to be a key facilitator for service access. These findings indicate that existing concerns of LGBTQA + competency among clinicians more broadly are echoed within mental health and suicide prevention services. Further education for mental health clinicians on the determinants of poor mental health in LGBTQA + young people may improve barriers to access in this population. Specific recommendations are provided to address issues in clinical practice and improve care of LGBTQA + young people.